2021
DOI: 10.1128/jvi.01399-20
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Herpes Simplex Virus 1-Induced Host Shutoff at the RNA Level

Abstract: Herpes simplex virus 1 (HSV-1) induces a profound host shut-off during lytic infection. The virion host shut-off (vhs) protein plays a key role in this process by efficiently cleaving host and viral mRNAs. Furthermore, the onset of viral DNA replication is accompanied by a rapid decline in host transcriptional activity. To dissect relative contributions of both mechanisms and elucidate gene-specific host transcriptional responses throughout the first 8h of lytic HSV-1 infection, we employed RNA-seq of total, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 86 publications
10
46
0
Order By: Relevance
“…We found that within 4h of HSV-1 infection of human cells there are dramatic changes to the host cell mRNA transcriptional program, with hundreds of genes losing Pol II occupancy and hundreds of others gaining Pol II. This is largely consistent with the transcriptional reprogramming observed in prior studies that also studied the effect of HSV-1 infection on host cell transcription in human cells looking at nascent mRNA production via PRO-seq or 4SU-seq rather than using Pol II ChIP-seq [10,11,13,39,40]. The effect of HSV-1 infection on Pol II occupancy in human cells is significantly different from that seen in mouse cells where only the reduction of Pol II occupancy was observed after 4h of infection with little to no activation [12], suggesting that the activation of Pol II transcription is a signature specific to the host species.…”
Section: Discussionsupporting
confidence: 86%
“…We found that within 4h of HSV-1 infection of human cells there are dramatic changes to the host cell mRNA transcriptional program, with hundreds of genes losing Pol II occupancy and hundreds of others gaining Pol II. This is largely consistent with the transcriptional reprogramming observed in prior studies that also studied the effect of HSV-1 infection on host cell transcription in human cells looking at nascent mRNA production via PRO-seq or 4SU-seq rather than using Pol II ChIP-seq [10,11,13,39,40]. The effect of HSV-1 infection on Pol II occupancy in human cells is significantly different from that seen in mouse cells where only the reduction of Pol II occupancy was observed after 4h of infection with little to no activation [12], suggesting that the activation of Pol II transcription is a signature specific to the host species.…”
Section: Discussionsupporting
confidence: 86%
“…In a recent study, we observed that the upregulation of the cellular protein Tripartite-motif 43 (TRIM43) upon HSV-1 infection is dependent on the embryonic transcription factor DUX4 7 , which was recently confirmed by Friedel et al 8 . DUX4 is a germline transcription factor exclusively expressed from the 4-cell to the 8-cell state, a short phase during human embryonic development [9][10][11] .…”
Section: Introductionsupporting
confidence: 56%
“…While recent studies have identified many interesting findings from total RNA analysis [131][132][133][134][135], general conclusions at the level of transcription are complicated by the varying technical methods and biological contexts utilized. Interestingly, nuclease activity of VHS globally reduced Pol II transcription of host genes, as was observed before with the SOX nuclease from murine gamma-herpesvirus 68 (MHV68) [111,136]. A proper discussion of host mRNA accumulation, its translation, and resulting outcomes on infection, particularly regarding innate immunity, is outside the scope of this review.…”
Section: Broader Network and Future Considerationsmentioning
confidence: 71%
“…Such techniques include those using chemical labeling (e.g., 4sU-Seq), long-read sequencing, or minimally normalization of polyadenylated RNA to chromatin-associated rather than total/total nuclear RNA. Chromatin-associated RNA closely matches nascent transcriptomes determined by chemical labeling in HSV infection [111], and is currently the most cost-effective and procedurally simple approach to differentiate co-from post-transcriptional events directly compatible with established HSV infection protocols for total RNA.…”
Section: Rna Processing In Splicing and Terminationmentioning
confidence: 87%
See 1 more Smart Citation